Hip and knee kinematics of the forward lunge one year after unicondylar and total knee arthroplasty. (October 2019) - De Vroey, Henri; Staes, Filip; Weygers, Ive; Vereecke, Evie; Van Damme, Geert; Hallez, Hans; Claeys, Kurt
Abstract: Patients with unicondylar knee arthroplasty (UKA) report higher functionality compared to those with total knee arthroplasty (TKA). However, these patients should also be assessed during more demanding tasks in order to appreciate their true functionality. The forward lunge (FL) is a motor task commonly used in clinics to evaluate functional recovery after knee replacement surgery. Unfortunately, clear evidence comparing FL kinematics between patients with UKA and TKA is still missing. The purpose of this study was to compare hip and knee joint kinematics during the FL between patients with UKA, TKA and controls. Twenty subjects (8 TKA, 6 UKA, 6 controls) underwent 3D motion analysis during a FL. Differences in hip and knee kinematics between groups were identified using statistical parametric mapping. We concluded that patients with TKA demonstrated reduced knee and hip flexion angles during the loaded phase of the FL, which could have been an attempt to unload the knee joint. This is in contrast to patients with UKA, who showed similar knee and hip joint kinematics compared to controls throughout the entire FL. It seems that retaining the cruciate ligaments is beneficial for the execution of a complex motor task such as the FL.